The Mediating Function of Institutional Cooperation in the Association between Rural Community Empower-ment and Corporate Social Responsibility: Data from Buffer Villages in Mesuji, Lampung - Widodo, Taufiq; Makhya, Syarief; Rifa’i, Ahmad (CV. Media Digital Publikasi Indonesia, 2026)
This study examines the mediating function of institutional collaboration in the relationship between rural community empowerment and Corporate Social Responsibility (CSR). This study is based on the collaborative governance framework and stakeholder theory, which highlight shared accountability and the active participation of commercial, governmental, and community actors in accomplishing sustainable development goals. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used as a quantitative methodology. 100 people were interviewed in conflict-affected buffer villages in Mesuji Regency, Lampung Province, Indonesia, including village administrators, community leaders, and members from local non-governmental organizations. The study found that CSR significantly increases institutional cooperation, which in turn increases rural communities' degree of empowerment. However, because the direct effect of CSR on empowerment was statistically negligible, institutional collaboration had a full mediating effect. These findings highlight the need for strong and active institutional synergy in order for CSR programs in disadvantaged rural settings to produce significant results.